Analysis of phosphorus speciation in primary sludge in the annual cycle - Bezak-Mazur, Elżbieta; Stoińska, Renata; Szeląg, Bartosz (Lviv Politechnic Publishing House, 2017)
The objective of the research was to investigate phosphorus speciation in sewage sludge in order to determine the amount of the element that can be assimilated by plants after the application of sludge for nature-related purposes. Since the possibility of using sludge for such purposes is of considerable importance, this paper analyses the content of different phosphorus speciation forms (including the bioavailable ones) in primary sludge. The studies’ results indicate that the maximum share of mobile forms (Ca-EDTA+Na- EDTA) in primary sludge in the annual cycle amounts to merely 46 %. This confirms the observation that in the examined period the hardly-available, organic phosphorus forms are dominant (fractions H2SO4 and NaOH). Therefore, after the application of primary sludge for nature-related purposes, only a small portion of phosphorus included therein is assimilated by plants.
Keywords: primary sludge; phosphorus speciation; application of primary sludge for nature-related purposes